World migration degree: Global migration flow in directed networks - Idan Porat; Lucien Benguigui (European Regional Science Association (ERSA), 2014)
Migration is an important aspect of human society. It has existed throughout history, but in modern times it takes a new form. We propose a new approach to the world migration phenomenon as two complex directed networks (immigration and emigration) were countries represents network nodes, and migration between countries represents directed links. We compose a general picture by evaluating both countries of sources of migrants and countries of receivers of migrants for which there are reliable data and statistics. Here we analyze the migration networks of 216 destination and source countries and territories (2006-2010), according to World Bank data. We evaluated two main parameters: degree (D) - the number of links of a country with the rest of the world; and weight (W) - the number of migrants to and from a country. Weight represents the extent of the migration to/from a country and degree represents the connectivity of a country to the global migration network. Statistical analysis of the degree and weight distributions offers a strong potential contribution to understanding of migration as global phenomena. Our findings suggest that source countries network has homogeneous distribution of weight and of degree and a strong correlation between them. The degree distribution of the source countries is Gaussian, indicating some universality in the emigration phenomenon. The distribution of the receiving countries shows a completely different pattern and we identify three main groups of countries and two main strategies of migration to destination countries: a) countries with high degree and high weight, representing a "global world" of high connectivity strategy; b) countries with low degree, representing a "local world" strategy with some high weight links; c) isolated countries of low connectivity and low migration flow. The migration is essentially a global and general process with similar characteristics and strategies regarding connectivity and flows. This indicates that questions about the origins and/or dynamics of the process. The efficiency of national policies can be asked for all countries since there are similarities between countries that are not considered as 'migration countries'. Consequently much general approach towards the phenomena is needed and a much larger view is required.
Keywords: 330; Immigration; Emigration; Networks; Degree